Considerations in designing trauma-focused interventions for displaced Afghan women - Ramos, Amaya Alexandra (Frontiers in Global Women's Health, 2023)
In light of the 2021 United States military withdrawal from Afghanistan, as well as the humanitarian crises of mass displacement and subsequent health system strain that have ensued, practitioners worldwide will need to develop a more nuanced understanding of the adverse life experiences that women from Afghanistan frequently endorse. As they bear a disproportionate impact of constraints within Afghan society, and as patriarchal systems affect most of their life domains, women from Afghanistan may present with high levels of baseline trauma upon resettlement, and health systems may seek to attenuate this distress; However, the nature of these traumatogenic events may shape women’s receptivity to psychosocial interventions, particularly those which are at least partially rooted in Western modalities. In the absence of sufficient literature on evidence-based interventions for this population, a diversity of ethnographic and clinical literature is synthesized, including literature on interventions alleged to be compatible with Afghan norms. As it will be essential to support Afghan women’s mental health following social reorganization on a massive scale, considerations arising from the interdisciplinary literature are offered so that they may inform the development of structured, trauma-focused interventions and so that the health systems with which they interface may be better prepared to serve them.